2019
DOI: 10.1080/15440478.2019.1629372
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical-Property-Based Comparison of Paper Yarn with Cotton, Viscose, and Polyester Yarns

Abstract: Cotton and oil-based fibre consumption is highly problematic because the growth of these materials often requires fertilisers and toxic pesticides. Less environmentally damaging alternative fibres are urgently required. This study investigates Manila-hemp paper-yarn textile fabrics. Manila-hemp (abacá) is a species of banana grown as a commercial crop in the Philippines, Ecuador, and Costa Rica. Knitted structures of paper, cotton, viscose, and polyester yarns are tested and compared. Tensile strength tests ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Researchers found that abrasion resistance is higher for the fibers that possess high tensile strength as these fibers have a great capacity to absorb friction under conditions of repeated stretching (Hamburger, 1945;Susich, 1954). Peterson et al (2021) examined the tenacity of fibers and found that cotton and viscose fiber show almost the same tenacity and force required to break where the polyester fabric has approximately double tenacity and force. In a comprehensive study on abrasion kinetics, they identified the relation of the structural parameter of fibers, yarns, and fabric to abrasion-resistance (Manich et al, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers found that abrasion resistance is higher for the fibers that possess high tensile strength as these fibers have a great capacity to absorb friction under conditions of repeated stretching (Hamburger, 1945;Susich, 1954). Peterson et al (2021) examined the tenacity of fibers and found that cotton and viscose fiber show almost the same tenacity and force required to break where the polyester fabric has approximately double tenacity and force. In a comprehensive study on abrasion kinetics, they identified the relation of the structural parameter of fibers, yarns, and fabric to abrasion-resistance (Manich et al, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of fashion requires the use of textile fabrics with new structures and properties for garment production. To ensure this, new types of threads and yarns with special structures and properties, which strongly influence their processing into textile fabrics, are used [1][2][3][4][5][6][7][8][9]. In textile processing, threads can withstand different interactionsrepeated extensions, bending, abrasion, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Since it shows some good mechanical properties and is a more sustainable alternative to cotton, the demand for paper yarn has been increasing [13]. For fashion and home textiles applications, the low shrinkage and absence of pilling of paper yarn products are desirable [14]. However, there are still properties that need to be enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Paper yarn and paper yarn-based textiles usually have several of the following drawbacks: low porosity, low flexibility, low strength, low elongation, low handleability, poor knittability, high stiffness, high grip, and high rigidity [11,14,15]. The unstable twist hinders the mass production of Hanji yarn [11].…”
Section: Introductionmentioning
confidence: 99%